PERAN ASEAN TOURISM FORUM DALAM MENINGKATKAN KUNJUNGAN WISATAWAN ASING DI INDONESIA (2009-2013) - Agung Setia Budi; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The title of this research is the The Role Of ASEAN Tourism Forum in Increasing Foreign Tourist Arrival in Indonesia 2009-2013. The method used was qualitative descriptive-analytic explanatif.The results of this research show that ASEAN Tourism Forum plays an important role in increasing foreign tourist arrivals in Indonesia. ASEAN Tourism Forum is a cooperation forum of tourism in the region of Southeast Asia pliers have a role increases the potential for tourism in Southeast Asia. ASEAN Tourism Forum also act as promoters, tourism investment forums, and policy makers in asean tourism standardization.The influence of the ASEAN Tourism Forum is evident from the development of the tourism industry in each country of Southeast Asia including Indonesia, since joining the tourism cooperation largest in Southeast Asia, Indonesia experienced a growth in tourism is very good, it is not free from the influence of the ASEAN Tourism Forum which includes there are M-ATM agenda that is where the ministers of tourism in the ASEAN region to exchange ideas to boost the tourism industry.Keyword : ASEAN, ATF, Tourism , Indonesia